2020
DOI: 10.1099/ijsem.0.004102
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic evaluation of the genus Nostoc and description of Nostoc neudorfense sp. nov., from the Czech Republic

Abstract: Cyanobacterial strain ARC8 was isolated from seepage coming into the river Dračice, Františkov, Czech Republic, and was characterized using a polyphasic approach. Strain ARC8 showed a typical Nostoc-like morphology and in-depth morphological characterization indicated that it is a member of the genus Nostoc. Furthermore, in the 16S rRNA gene phylogeny inferred using Bayesian inference, maximum likelihood and neighbour joining methods, strain ARC8 clustered within the Nostoc sensu stricto clade. The phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Vegetative cells may be cylindrical, barrel-shaped or spherical, solitary intercalary or terminal heterocytes and spherical or oblong akinetes [4]. The absence of strong and distinct synapomorphic features, complex life cycle events and vast morphological heterogeneity makes Nostoc a morphologically complex genus [5, 6]. With the application of a polyphasic approach, the last one and half decades have proved very crucial in the taxonomy of Nostoc and its related morphotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetative cells may be cylindrical, barrel-shaped or spherical, solitary intercalary or terminal heterocytes and spherical or oblong akinetes [4]. The absence of strong and distinct synapomorphic features, complex life cycle events and vast morphological heterogeneity makes Nostoc a morphologically complex genus [5, 6]. With the application of a polyphasic approach, the last one and half decades have proved very crucial in the taxonomy of Nostoc and its related morphotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, some studies have highlighted that most cyanobacteria extracts, and even those species or strains that do not produce toxin, are more harmful than purified cyanotoxins by showing that cyanobacteria contain other toxic compounds beyond known toxins [ 2 , 31 , 90 , 123 ]. Toxicity in cyanobacteria is not taxa- but clone-related, and by considering the polyphyly in some genera like Nostoc , it should be elucidated if toxin producers and nonproducers belong to the same species [ 126 ]. Studies have already shown that the same species can produce toxins, or not, and even the same species may produce different toxins according to the geographical location or the physic-chemical parameter of habitats [ 2 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nostoc colonies in the Monte Alegre and Iturbide springs sites contained Chironomidae larvae, which modify their architecture to the appearance of an "ear." The second group contains the downland and calcareous Tambaque population, which are from warm water (23.5°C) highly mineralized TA B L E 2 Morphological characteristics (average, minimum, and maximum, n = 50) of the Nostoc populations in streams from central Mexico and other species of the genus (Cai et al, 2021;Komárek, 2013;Mesfin et al, 2020;Singh et al, 2020). (1528 μS · cm −1 ), high DO (8.4 mg · L −1 ), low nutrients (DIN 0.097 mg · L −1 and soluble reactive phosphorous 0.02), and high current velocity (0.80 m · s −1 ).…”
Section: Ecology and Distributionmentioning
confidence: 99%